Influence of hot deformation on the electrochemical behavior of natural oxides of hipped Ti6Al4V. (May 2015) - De Fenzo, A.; Scherillo, F.; Astarita, A.; Testani, C.; Squillace, A.; Bellucci, F.
Highlights: The microstructure of TI6Al4V specimens depends on compression process parameters. The electrochemical behavior of natural oxide depends on microstructure. The deformation process induces porosity in specimens treated above the β-transus. Abstract: The correlation between microstructure of Hot Isostatic Pressing Ti6Al4V, hot deformed, and his electrochemical behavior, has been studied. The specimens have been compressed at three temperatures (900 °C, 1000 °C, 1100 °C), and three different strain rates (0.01 s −1, 0.1 s −1, 1 s −1 ). Optical and SEM observations have been performed and porosity cluster have been observed for specimens deformed at 900 °C and 1100 °C at 0.1 s −1 and 1 s −1 . Potentiodynamic polarization and Electrochemical Impedance Spectroscopy (EIS) have been carried out in NaCl 3.5 wt% solution and the data modeled by Zplot© software. Electric parameters collected, confirmed that the microstructure influences electrochemical behavior of specimens.